CompTIA Linux+ ; LPIC-1 : complete video course - Vugt, Sander van (LiveLessons (Indianapolis, Ind.), 2015)
CompTIA Linux+/LPIC-1 Complete Video Course provides a solid understanding of all topics that candidates need to master to pass the CompTIA Linux+/LPIC-1 Certification. CompTIA Linux+/LPIC-1 Complete Video Course offers almost 13 hours of training covering all objectives on the CompTIA Linux+ and Linux Professional Institute LPIC-1 exams. 28 lessons in 7 modules divided into separate exam sections make sure you learn every topic included in the exam objectives. This course also serves as an introduction for people interested in learning basic Linux administration skills. The videos provide thorough coverage of command-line skills that work on multiple distributions and prepares anyone who wants to acquire in-depth knowledge of common Linux tasks. The CompTIA Linux+/LPIC-1 Complete Video Course prepares you for the CompTIA Linux+ powered by LPI certification, which grants CompTIA Linux+, LPIC-1, and the SUSE Certified Linux Administrator (CLA) certifications, so you can earn three industry-recognized certifications at once.